Assess electricity quality by means of fuzzy generalized index - Tymchuk, Sergiy; Miroshnyk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2015)
Most of branching and length of distribution networks, unstable and heterogeneous nature of the load, low observability of electric networks, lack of information about the topology and load during the period of time do not allow the operating personnel to obtain reliable values of quality of electric energy and therefore accurately determine the degree of influence of poor electricity on the mode of operation, the service life of specific groups of consumers. The uncertainty of the initial information needs to be revealed. The existing calculation methods are mainly deterministic and do not allow to take into account the uncertainty of the initial information. To accomplish this task are invited to submit indicators of quality of electric energy in the form of triangular fuzzy numbers and quality standards – in the form of trapezoidal fuzzy intervals. Fuzzy quality score is determined based on the processing of measurement results, and the fuzzy quality standards are based on the permissible range given in the regulations. The degree of conformity of fuzzy values of the fuzzy index of electricity quality standards proposed for the area to assess the figure formed by the intersection of the membership function. Considering the characteristics of the individual groups of loads , it is proposed to assess the quality of electricity for these groups separately by fuzzy integral indicator. Expressions are given for the determination of the integral indexes of electricity quality for different types of loads. In particular, we present integrated indexes of electricity quality unbalance and for non-sinusoidal motor, lighting load, and devices with a microprocessor control unit. The importance of these results is that the first time it is possible to improve information quality assessment of electricity in the uncertainty of the initial information. And, most importantly, if you know the type of load, it is possible to consider only the quality parameters of electric energy, which adversely affect the operation of a particular electroreceivers.